Surgical outcomes associated with postoperative atrial fibrillation after robotic-assisted pulmonary lobectomy: retrospective review of 208 consecutive cases - Ng, Emily P.; Velez-Cubian, Frank O.; Rodriguez, Kathryn L.; Thau, Matthew R.; Moodie, Carla C.; Garrett, Joseph R.; Fontaine, Jacques P.; Toloza, Eric M. (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Background: In this study, we sought to investigate the effect of post-operative atrial fibrillation (POAF) after robotic-assisted video-thoracoscopic pulmonary lobectomy on comorbid postoperative complications, chest tube duration, and hospital length of stay (LOS). Methods: We retrospectively analyzed prospectively collected data from 208 consecutive patients who underwent robotic-assisted pulmonary lobectomy by one surgeon for known or suspected lung cancer. Postoperatively, 39 (18.8%) of these patients experienced POAF during their hospital stay. The occurrence of postoperative complications other than POAF, chest tube duration, and hospital LOS were analyzed in patients with POAF and without POAF. Statistical significance (P≤0.05) was determined by unpaired Student’s t-test or by Chi-square test. Results: Of patients with POAF, 46% also had other concurrent postoperative complications, while only 31% of patients without POAF experienced complications. The average number of postoperative complications experienced by patients with POAF was significantly higher than that experienced by those without POAF (0.9 vs. 0.4, P